2020
DOI: 10.3390/separations7040070
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Thermal and Flow-Based Modulation in Comprehensive Two-Dimensional Gas Chromatography—Time-of-Flight Mass Spectrometry (GC × GC-TOFMS) for the Analysis of Base Oils

Abstract: Base oils are produced by refining crude oil or through chemical synthesis. They are a key component of engine oils. With an immense range of carbon numbers and boiling points, analyzing such complex mixtures is very difficult. The need to monitor industrial petroleum processing steps, as well as to identify petrochemical environmental pollutants, drives the search for improved characterization methods. Comprehensive two-dimensional gas chromatography (GC × GC) is one of the best tools for that. The modulator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…By using the EI method, molecules can be identified based on analyzing their fragmentation mass spectra and matching them with a published EI MS library (NIST library). 442 Many publications have been reported using GC × GC-EI-TOF-MS for analyzing the aromatic components in the petroleum samples. [443][444][445] In one of the scientific papers published by Hamilton et al 102 demonstrated the usefulness of GC × GC-EI-TOF-MS for the analysis of the feed and the product from the hydrocracker coal liquefaction process.…”
Section: Comprehensive 2d Gas Chromatography Coupled To Time-of-fligh...mentioning
confidence: 99%
See 2 more Smart Citations
“…By using the EI method, molecules can be identified based on analyzing their fragmentation mass spectra and matching them with a published EI MS library (NIST library). 442 Many publications have been reported using GC × GC-EI-TOF-MS for analyzing the aromatic components in the petroleum samples. [443][444][445] In one of the scientific papers published by Hamilton et al 102 demonstrated the usefulness of GC × GC-EI-TOF-MS for the analysis of the feed and the product from the hydrocracker coal liquefaction process.…”
Section: Comprehensive 2d Gas Chromatography Coupled To Time-of-fligh...mentioning
confidence: 99%
“…Compositional elucidation of heavy petroleum base oil GC×GC-EI/PI/CI/FI-TOFMS Boswell et al, 442 Characterization of base oils through thermal and flow modulators Bowman et al, 490 2020 Naphthenic acids in oils Gieleciak et al, 491 2020 Sulfur-containing hydrocarbons in the bitumen-derived gas oil GC×GC-TOFMS/SCD/FID, Karakhanov et al, 492…”
Section: Gp-mse (Gas Purge Microsyringe Extraction)mentioning
confidence: 99%
See 1 more Smart Citation
“…Both types of modulator technologies have been extensively applied across various applications. Following references involve the use of CFT reverse fill/flush modulation [19][20][21][22][23][24][25][26][27], while [28][29][30][31][32][33][34] employ INSIGHT reverse fill/flush modulator.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent analysis of the brominated products by a separation method, such as one-dimensional (1D) GC, facilitates a more precise analysis of the olefin content. , However, 1D-GC is inherently limited in its peak capacity; thus, the total number of mixture components that can be resolved within a reasonable analysis time is also limited. , Comprehensive two-dimensional (2D) GC, or GC×GC, provides an enhancement in peak capacity of about an order-of-magnitude, , increased detectability, , and additional selectivity with compound class-ordered separations. Coupling GC×GC with time-of-flight mass spectrometry (GC×GC-TOFMS) creates a powerful instrument, well-suited to the characterization of petroleum-based fuels. Unsurprisingly, several researchers have investigated the utility of GC×GC to analyze olefins in various mixtures, including Fischer–Tropsch products, commercial dodecenes, , diesel, and unsaturated fatty acids …”
mentioning
confidence: 99%